Readiness aspects in education sector to succeed in Industry 4.0 (IR 4.0): a review / Nurulanis Ahmad @ Mohamed ... [et al.] - Ahmad @ Mohamed, Nurulanis; Johari, Noraini; Mohd, Thuraiya; Senawi, Asma (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
This paper reviews the readiness aspects in the education sector for engaging a new frontier of IR 4.0 and identifies possible ways of succeeding in IR 4.0. A new wave of IR 4.0 has created a greater impact on the whole industry and the education sector is no exception. IR 4.0 has revealed technological advancements using automated machine systems and the Internet of Things is becoming a priority in human life. This is in tandem with the aims of IR 4.0 of ensuring the effectiveness and flexibility in the operations of the industry. Indeed, IR 4.0 benefits are numerous. However, extensive utilization through the Internet of Things (IoT) and digital systems have caused major changes in the educational landscape, i.e., educational content, delivery/pedagogy, and its management structure. Thus, the education sector is among the sector facing disruptive challenges due to the speed of innovations. Are we ready? This study found that education needs to consider readiness aspects in terms of psychological, environmental, financial, technological skills and curriculum content to meet the changes brought about by IR 4.0.